Lateral light transfer ensures efficient resource distribution in symbiont-bearing corals - Larkum, Anthony William D. (2018)
Coral tissue optics has received very little attention in the past, although the interaction between tissue and light is central to our basic understanding of coral physiology. Here we used fibre-optic and electrochemical microsensors along with variable chlorophyll fluorescence imaging to directly measure lateral light propagation within living coral tissues. Our results show that corals can transfer light laterally within their tissues to a distance of ~2 cm. Such light transport stimulates O2 evolution and photosystem II operating efficiency in areas >0.5–1 cm away from direct illumination. Light is scattered strongly in both coral tissue and skeleton, leading to photon trapping and lateral redistribution within the tissue. Lateral light transfer in coral tissue is a new mechanism by which light is redistributed over the coral colony and we argue that tissue optical properties are one of the key factors in explaining the high photosynthetic efficiency of corals.